COMPUTERIZED INVENTORY SYSTEM WITH MULTIUSER FOXBASE + REV 2.00 IN MENTENG MOTOR CAR DISTRIBUTOR - Yudi Irawan Chandra; Aqwam Rosadi Kardian,S.kom.,MMSI (Jurnal Sistem Informasi, 1998)
Satisfactory service is the key to business done by Menteng Motor Car Distributors. One of the efforts being undertaken to meet these demands is to build a computerized system that can handle the activities of the purchase, sale and supply of goods, so it will be able to increase the productivity of the company. To meet these needs, the author conducted the analysis and design of a computerized inventory system that can handle the activities of buying, selling and handling of inventory. Analysis of the authors do is to conduct research directly to the field by interviewing the parties involved to get their feedback about the working procedures in the administration of Menteng Motor Car Distributors, and by reading the reading books as information sources.